The Importance of Information for Effective University–Firm Technology Transfer: The Case of ICAT–UNAM (American Journal of Management, 2021)
As part of their mission, faculties, centers, and research institutes of public universities in Mexico, develop technology products to a certain level of maturity. Normally, project development teams are devoted to building the hardware and software of the technology products but rarely deal with the commercial and technology management information required to advance the business plan for technology transfer. Socioeconomic, organizational, and new project development information is normally prepared by personnel in the university’s technology transfer office. Using a case study methodology, this article highlights the importance and the value of the information provided by technology studies undertaken throughout the different phases of a Research Development and Innovation (R&D+i) project, until the point of technology transfer negotiations. The presented study involves the case of a Mexican public R&D institute, the National Autonomous University of Mexico (UNAM).
Keywords: management; technical and commercial information reports; technology transfer; Mexican Public University